HUBUNGAN KESEPIAN DAN KECENDERUNGAN BERSELINGKUH PADA WANITA YANG MENJALANI HUBUNGAN PERNIKAHAN JARAK JAUH (PSIKOLOGI KONSELING, 2020)
This study aims to examine the relationship of loneliness and the tendency to cheat on women who undergo long-distance marital relationships. The hypothesis of this study is that there is a positive relationship between loneliness and the tendency to have an affair in women undergoing long-distance marriages. Participants in this study amounted to 31 subjects obtained by accidental sampling technique, with the criteria of women undergoing long-distance marital relationships for at least two months. Data were collected on a lonely scale from Ucla Version 3 and the scale of cheating tendencies. Data analysis used Pearson correlation with the help of SPSS 23. The results showed a positive relationship between loneliness and the tendency to have an affair in women undergoing long-distance marriage (r = 0.501; p = 0.002).Keywords: Loneliness, Tendency To Cheat, Women Undergoing Long-Distance Marriage.